2016
DOI: 10.1364/oe.24.017593
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controllable plasmonic enhanced coherent random lasing from dye-doped nematic liquid crystals containing Au nanoparticles

Abstract: An electrically controllable plasmonic enhanced coherent random lasing from the dye-doped nematic liquid crystal containing Au nanoparticles is demonstrated. To achieve the optimal control of the RL properties, the polarization of the pump light should be parallel to the rubbing direction of the cells. The lasing output intensity is direction-dependent and the substantial output distributes in an angle range of 0°~30° deviating from the direction of the pump stripe. The coherent feedback associated with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Over the past decade, plasmonic random lasers have attracted considerable attention because of their great potential for use as display and sensing devices. [1][2][3][4][5][6][7][8] The lasing threshold of a plasmonic random laser is much lower than that of a conventional random laser because of its large scattering cross-section and the localized surface plasmon resonance of the metal nanoparticles (NPs) used in the structure. [9][10][11][12][13] Additionally, red-greenblue (RGB) plasmonic random lasers have been studied as potential multicolor output devices.…”
mentioning
confidence: 99%
“…Over the past decade, plasmonic random lasers have attracted considerable attention because of their great potential for use as display and sensing devices. [1][2][3][4][5][6][7][8] The lasing threshold of a plasmonic random laser is much lower than that of a conventional random laser because of its large scattering cross-section and the localized surface plasmon resonance of the metal nanoparticles (NPs) used in the structure. [9][10][11][12][13] Additionally, red-greenblue (RGB) plasmonic random lasers have been studied as potential multicolor output devices.…”
mentioning
confidence: 99%
“…Because the laser action is correlated with the orientational direction of liquid crystals [15], it could respond to the molecular reorientation by a variety of external stimuli. In fact, the wavelength, intensity and polarization of the random laser in NLCs can be controlled by electrical [16][17][18][19], thermal [13,20] and magnetic [19] stimuli, and the alignment of LC cells [15,21]. In particular, the optical switching owing to the molecular reorientation in a magnetic field [22] has some advantages in remote operability [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, a wide range of materials, such as semiconductor [7], π-conjugated [8], human tissues [9], quantum dots [10], metallic nanoparticles [11,12], polymers [13], and liquid crystals (LCs) [14][15][16] have been used to realize random lasers. Metal nanoparticles, such as gold (Au) nanoparticles and silver (Ag) nanoparticles are often used to enhance the performances of random lasers [11,12,[17][18][19][20]. For example, Dice et al [17] reported in 2005 that the random lasers formed by suspending Ag nanoparticles in the laser dye solution.…”
Section: Introductionmentioning
confidence: 99%